PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA INTERAKTIF WORDWALL TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SD INPRES 3/77 BUNE KABUPATEN BONE - Nur Isnain Ali; Fitri Yanty Muchtar; Syarifah Aeni Rahman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to determine the effect of the Problem Based Learning (PBL) model assisted by Wordwall interactive media on the science and social studies (IPAS) learning outcomes of fifth-grade students at SD Inpres 3/77 Bune. The study addresses the low science literacy and suboptimal learning processes observed at the school. This quantitative research used a pre-experimental method with a one-group pretest-posttest design. The sample consisted of 17 students selected through total sampling. Data collection techniques included multiple-choice tests and observation sheets. Data were analyzed using descriptive and inferential statistics, specifically the Paired Sample T-Test. The results showed that the average pretest score of 68.24 increased to 87.06 in the posttest, indicating an increase of 18.82 points. Hypothesis testing obtained a significance value (Sig. 2-tailed) of <0.001, which is smaller than 0.05. It can be concluded that the application of the PBL model assisted by Wordwall interactive media has a significant positive influence on the IPAS learning outcomes of fifth-grade students at SD Inpres 3/77 Bune.